Faktor Determinan Konsumsi Sayur Dan Buah Pada Anak SDN 01 Hajimena, Lampung Selatan Tahun 2023 - Antun Rahmadi; Dewi Sri Sumardilah; Endang Sri Wahyuni; Ryan Agusta (JGK:Jurnal Gizi dan Kesehatan, 2023)
Background: Fruit and vegetable have advantages as a source of antioxidants, fiber, vitamins and minerals which play an important role in growth and disease prevention. Low vegetable and fruit intake in children is associated with a risk of health problems in adulthood. Purpose: To determine the relationship of knowledge, availability, and preferences with the consumption of vegetables and fruit in elementary school children. Methods: The research location is SDN 01 Hajimena, Natar District, South Lampung. There were 66 students who participated in this study. Participants were grade 5 and 6 students who were taken by systematic random sampling of 199 students. The design of this study was cross-sectional, when data collection was conducted in May 2023. Data analysis used the Chi-Squared test. Result: The results showed that the consumption of vegetables and fruit for school children was low. The average consumption of vegetables is 159 grams/day while fruit consumption is 102 grams/day. Conclusion: Knowledge, availability, preferences of vegetables and fruit correlated with vegetable and fruit consumption (p<0.05).